Vernacular Heritage and Earthen Architecture: Contributions for sustainable development - Correia, Mariana (2022)
In a continuously changing world, there has been a growing interest in the protection of vernacular heritage and earthen architecture. The need to protect and enhance this fragile heritage via intelligent responses to threats from nature and the environment has become evident. Historically, vernacular heritage research focussed on philosophical aspects and surveys, while earthen architecture studies emphasized earthen material and construction techniques. However, for these particular forms of heritage to survive, academic research had to shift its focus, so as to respond to new challenges. Vernacular Heritage and Earthen Architecture gathers contributions of key international researchers from 50 countries, and covers a wide variety of topics: • Cultural heritage and building cultures • Materials and construction techniques • Territory and environmental adaptation • Energy effi ciency and sustainable design • Natural hazards and risk mitigation • Education and research focus Vernacular Heritage & Earthen Architecture: Contributions for Sustainable Development discusses the threats that vernacular and earthen heritage are facing, and reflects on their important contribution to sustainable development. The book will prove to be a valuable source of information for academics, researchers and professionals in the fields of vernacular heritage, conservation, architecture, civil engineering and construction, and can be used as a reference text for undergraduate and post-graduate courses in vernacular heritage and earthen architecture.